Phagocytosis Exhibited by Neonatal Hepatocytes at the end of Murine Liver Hematopoiesis - An Ultrastructural Study - Ichiro KUMANO; Yuji SONODA; Kazunobu SASAKI (KAWASAKI MEDICAL JOURNAL, 2006)
To clarify hepatocyte phagocytosis of hematopoietic cells and their disposal processes in livers at the terminal point of liver hematopoiesis, neonatal mouse livers were examined by transmission electron microscopy. From two to ten days after birth, hepatocytes containing large inclusions appeared, and the inclusions were secondary phagolysosomes derived from hematopoietic cell elements. The heterophagosomes contained erythroblasts, nuclei expelled from erythroblasts, neutrophils and eosinophils, and, neutrophils, in particular, are the most frequently engulfed. These hematopoietic cells are degradated in the phagosomes. In the early stage, they are characterized by nuclear chromatin condensation, and then collapse of nuclei and cytoplasmic structures was followed. In the final stage of digestion, the phagosomes included residual bodies, such as dense bodies and myelin bodies. In the early postnatal period, in addition to sinusoidal macrophages, hepatocytes played a temporary role in removal of blood cell elements within liver lobules, and residual bodies appeared to be excreted into bile canaliculi.